Influences of e-service quality toward customer loyalty of dropee / Zulfahmi Zulkifle - Zulkifle, Zulfahmi (2018)
E-commerce is online platform where users can buy and sell through online in convenient way. Since, ecommerce B2C is quickest developing in Malaysia it will give Dropee, B2B ecommerce platform the big impact and hard time to maintaining in this modernization of technology hence Dropee is the new startup B2B company. Hence the increases of online purchasing behavior and B2C ecommerce platform is getting more reliable and trustworthiness from users will giving a shock shutdown for B2B ecommerce platform once B2C ecommerce such as Lazada and Shopee enhance their business model to B2B platform unless Dropee can enhance their e-service quality. Moreover, increases of number of users that register to Dropee website also important to Dropee in order to maintaining them using service that provided. This study attempts to investigate the relationship between e-services quality and customer loyalty of Dropee. There are several attributes such as information availability and content, ease of use and usability, privacy and security and last but not least fulfilment toward customer loyalty of Dropee.•This study used quantitative approach. The primary and secondary data collection. Survey had been distributed to 263 Dropee user by using simple random sampling technique. As result, data interpretation by using statistical package for social science (SPSS) to finding normality, reliability, descriptive, regression and correlation analysis. In conclusion, information availability and content are significant relationship with customer loyalty. meanwhile the others are rejected significant. Thus, this study is to help Dropee to improve better to giving out the best e-service quality to improve their customer loyalty.